Arbitration Treaty between the United States and the Netherlands Palmas Island Affair Miangas a model - Saeed Al-Baydani, Ibrahim (Journal of College of Education, 2022)
The Although the historical study of the issue of arbitration in international relations falls within the framework of the specialization and academic interest of the author in the field of diplomatic history and the history of international relations, it is another turning point and interest that reinforces his previous studies in this field, as he presents for the first time historical studies in another field One of the fields of study of the history of international relations, which is the field of historical legal studies, in addition to that the research gives evidence and examples from the experiences of international arbitration, and thus from documenting the link between history and law, the study of the development of laws and evidence of arbitration provides historical studies of important legal issues that contribute to spreading and increasing awareness of the law On the other hand, the researcher confirms the importance of the issue of arbitration in international relations and the area of interest that he occupied within the framework of these relations, in addition to that, the American historical document remained present in this research because of its importance in the research for the ideas, information and trends it presents.